Legal Protection for Third Parties in Good Faith on Actio Pauliana Litigation in Bankruptcy Proceedings - Wiguna, I Nyoman; Andaretna, Laila Maghfira; Budianto, Michael Christian; Vala, Tanaya Anindhita (Yuridika, 2024)
Actio Pauliana in bankruptcy, as stipulated under Law Number 37 of 2004, empowers the Curator to seek the annulment of transactions undertaken by the bankrupt debtor, causing harm to the bankrupt estate. Actio Pauliana requires proof that a third party, the debtor's transaction partner is proven to not have acted in good faith, as outlined in the law. However, the legislation lacks clarity on the criteria safeguarding third parties in good faith against Actio Pauliana claims. This research employs a doctrinal research method involving a statute, conceptual, case, and comparative approach. The novelty of this research expounds upon and elucidates the need for amendments to Law Number 37 of 2004, particularly concerning the criteria protecting third parties in good faith. These criteria could be differentiated based on the third parties' position in bankruptcy and the nature of the objects constituting the bankrupt estate, including tangible and intangible movable objects, unregistered objects, immovable objects, and/or registered objects. Furthermore, proposed improvements to the law include refining provisions related to creditors' right to file Actio Pauliana lawsuits, affirming a one-year period rather than a deadline, and addressing timelines within Actio Pauliana lawsuits. Actio Pauliana claims should only be submitted after the debtor's bankruptcy declaration, excluding the Suspension of Debt Payment Obligations (PKPU) process. In conclusion, the research proposes possible solutions, such as the issuance of a Regulation (Perma) or a Circular Letter (SEMA) by the Supreme Court, containing the essential improvements to Law Number 37 of 2004.